Al‐Anon family groups' newcomers and members: Concerns about the drinkers in their lives. (15th March 2014) - Timko, Christine; Cronkite, Ruth; Laudet, Alexandre; Kaskutas, Lee Ann; Roth, Jeffrey; Moos, Rudolf H
<x xml:space="preserve">Abstract</x> Background and Objectives Despite Al‐Anon's widespread availability and use, knowledge is lacking about the drinkers in attendees' lives. We filled this gap by describing and comparing Al‐Anon newcomers' and members' reports about their "main drinker" (main person prompting initial attendance). Methods Al‐Anon's World Service Office mailed a random sample of groups, yielding completed surveys from newcomers (N = 362) and stable members (N = 265). Results Newcomers' and members' drinkers generally were comparable. They had known their drinker for an average of 22 years and been concerned about his or her's drinking for 9 years; about 50% had daily contact with the drinker. Most reported negative relationship aspects (drinker gets on your nerves; you disagree about important things). Newcomers had more concern about the drinker's alcohol use than members did, and were more likely to report their drinkers' driving under the influence. Drinkers' most frequent problem due to drinking was family arguments, and most common source of help was 12‐step groups, with lower rates among drinkers of newcomers. Concerns spurring initial Al‐Anon attendance were the drinker's poor quality of life, relationships, and psychological status; goals for initial attendance reflected these concerns. Discussion and Conclusions The drinker's alcohol use was of less concern in prompting initial Al‐Anon attendance, and, accordingly, the drinker's reduced drinking was a less frequently endorsed goal of attendance. Scientific Significance Family treatments for substance use problems might expand interventions and outcome domains beyond abstinence and relationship satisfaction to include the drinker's quality of life and psychological symptoms and in turn relieve concerns of family members. (Am J Addict 2014;23:329–336)